Occurrence and spatial distribution of microplastics, and their correlation with petroleum in coastal waters of Hainan Island, China. (1st February 2022) - Gao, Liu; Wang, Zezheng; Peng, Xianzhi; Su, Yuanyuan; Fu, Pengcheng; Ge, Chengjun; Zhao, Jinjin; Yang, Liang; Yu, Huamei; Peng, Licheng
Abstract: In this study, the distribution, abundance, morphology, and composition of microplastics (MPs) in surface seawater and sediment of Hainan Island were systematically investigated. Seawater and sediment samples were collected from six functional zones, including harbor, industrial district, sparsely populated area, tourist area, residential area, and aquaculture area. The abundance of MPs in seawater was 0.46–19.32 items/L, with an average of 2.59 ± 0.43 items/L, which were similar to those detected in the South China Sea (e.g., Nansha (1.25–3.20 items/L) and Xisha (2.57 ± 1.78 items/L)). The highest level was detected in Qinglan Bay Estuary, and the lowest was in Sanya West Island. The abundance of MPs in sediment was 41.18–750.63 items/kg, with an average of 372.47 ± 62.10 items/kg; the highest concentration was detected at Tanmen Port, and the lowest was in Lingao sea area. It was detected that the MPs with smaller size exhibited a higher concentration in seawater. MPs were commonly black and white, and predominantly linear and fragmented in shape. Polyethylene terephthalate (PET) was the dominant polymer, which might be derived from laundry wastewater. The petroleum concentration was 0.02–0.21 mg/L in the investigated area, with harbors being the most severely polluted areas. Furthermore, this study also found that MPs pollution was positively correlated with petroleum in seawater, indicating similarities between MPs and petroleum-based sources of pollution. This study identifies the contamination and characteristics of MPs and their correlation with petroleum in Hainan Island, the biggest island in the South China Sea, providing important data for further research on protecting marine ecosystems. Graphical abstract: Image 1 Highlights: Water quality of the coastal waters of Hainan Island was threatened by MPs. The predominant color, shape and polymer type of MPs were black, linear and PET. The highest abundance and diversity of MPs were detected in harbor area. MPs abundance was positively correlated with petroleum in seawater.